Reseña de: Sheldon, Rose Mary, Guarding the Caesars. Roman Internal Security under the Flavian Dynasty - Bermejo-Rubio, Fernando (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2024)
Reseña de: Sheldon, Rose Mary, Guarding the Caesars. Roman Internal Security under the Flavian Dynasty, Rowman & Littlefield, Lanham / Boulder / New York / London, 2023, 413 pp. ISBN: 9781538181140.